ALTERNATIF PERUMUSAN KEBIJAKAN PEMULIHAN EKONOMI NASIONAL DALAM MASA PANDEMI COVID19 - Ona Martha Nurron (Universitas Halu Oleo, 2021)
The purpose of this research is to explore the process of national economic recovery policy formulation, how it was regulated, and searching the alternatives to overcome economic problems along with its benefit and value for businesses and the general public amidst the covid19 pandemic. The qualitative descriptive method is utilized based on the systematic literature review of secondary data. Policy alternatives are determined by comparing policies in two countries, Indonesia and the United States of America. By observing the impact and cause beyond the scope, policy alternatives could be more easily identified, selected, and implemented according to their political feasibility. In accordance with identifying policy alternatives model which divide into two categories, Indonesia’s government employed temporary research analysis while United States federal governments were applying status quo analysis.